Pickles from Edible Oyster (Crassostrea madrasensis) Meat - G., Sugumar; G., Jeyasekaran; P., Jeyachandran (Fishery Technology, 2025)
Two recipes were formulated for the preparation of pickles from edible oyster (Cassostrea madrasensis) meat; a conventional hot spicy taste and a sweet and sour taste. Biochemi- cal, microbiological and organoleptic tests were carried out during storage to assess the shelf ife. The pickles had a shelf life of about 6 months at ambient temperature and organolephcally both the pickles had good acceptability.